2012
DOI: 10.1097/qad.0b013e32834f33e8
|View full text |Cite
|
Sign up to set email alerts
|

mRNA-based dendritic cell vaccination induces potent antiviral T-cell responses in HIV-1-infected patients

Abstract: Therapeutic immunization with dendritic cells was safe and successful in raising antiviral cellular immune responses, including effector CD8(+) T cells with virus inhibitory activity. The stimulation of those potent immunological and antiviral effects, which have been associated with control of HIV-1, underscores the potential of dendritic cell vaccination in the treatment of HIV-1. The incomplete nature of the response in some patients helped to identify potential targets for future improvement, that is incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 36 publications
1
66
0
1
Order By: Relevance
“…The 13 clinical trials published so far suggest that DC immunotherapy in HIV-1 infection can elicit HIV-1 specific immunological responses. However, only five of these studies reported virological responses to immunization, 44,45,51,52,55 three have not assessed virological responses 47,50,53 and five failed to show any response. 43,46,48,49,54 Recently, our group reported the results of a blinded placebo controlled trial of a therapeutic vaccine using autologous MD-DC pulsed with autologous heatinactivated whole HIV.…”
Section: Clinical Trials With Md-dcbased Therapeutic Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 clinical trials published so far suggest that DC immunotherapy in HIV-1 infection can elicit HIV-1 specific immunological responses. However, only five of these studies reported virological responses to immunization, 44,45,51,52,55 three have not assessed virological responses 47,50,53 and five failed to show any response. 43,46,48,49,54 Recently, our group reported the results of a blinded placebo controlled trial of a therapeutic vaccine using autologous MD-DC pulsed with autologous heatinactivated whole HIV.…”
Section: Clinical Trials With Md-dcbased Therapeutic Vaccinesmentioning
confidence: 99%
“…72 At least 4 clinical trials with mRNA electroporated DC-based vaccines have been performed. 50,[52][53][54] The results of these clinical trials have been promising, but transfection of mRNA into DCs for adoptive transfer is cumbersome. Additional data in mouse tumor models obtained by Van Lint et al 68 suggested that intranodal immunization with mRNA based therapeutic vaccine encoding a tumor associated antigen plus a mixture of antigen presenting cell activation molecules, including CD40L, a constitutively active variant of Toll-like receptor (TLR) 4 and CD70 has the potential to efficiently augment the induction of tumor-specific immune responses compared with a mRNA electroporated DC-based vaccine.…”
Section: In Vivo DC Targeting Immunogensmentioning
confidence: 99%
“…Hence, DCs have caught the attention for their use as therapeutic agents for immunotherapy of cancer 6 and infectious diseases, such as human immunodeficiency virus (HIV). 7,8 Research on DC-based immunotherapy is currently focusing on the vaccine-mediating effects on the adaptive immune system, aiming at inducing (tumor)antigen-specific cytotoxic T lymphocytes (CTLs). Less extensively studied is the effect of DC-based immunotherapy on gd T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the use of autologous DCs as vaccine vectors may surpass the adverse effects of preexisting immunity to commonly investigated viral vectors. DC-based vaccines containing different antigens have been investigated, with promising effects, and they seem to be well tolerated in vivo (27,40,51). Still, several questions regarding the best immunogen to include in the formulations, the inoculation route, adjuvants, and timing, among other factors, remain ill defined.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most encouraging studies on DC-based immunotherapy against HIV, including human clinical trials, were performed with autologous inactivated virus or gag mRNA (27,28,40). Therefore, we investigated the magnitude and immune response profile of Lg-DC strategy in comparison to the ones induced by iHIV-or gag N -based DC therapy.…”
Section: Lg-dcs Induce Higher Acute and Memory Immune Response In Commentioning
confidence: 99%